1990
DOI: 10.1210/endo-126-2-1047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vasopressin on Insulin Secretion and Inositol Phosphate Production in a Hamster Beta Cell Line (HIT)

Abstract: The recent isolation of vasopressin (VP) from the rat and human pancreas led us to investigate the effects of VP on insulin secretion. In the SV 40-transformed hamster beta cell line (HIT), 0.1-1.0 nM VP caused rapid stimulation of insulin secretion. Slight but significant inhibition of insulin secretion was observed in the presence of 10 pM VP. These effects of VP on insulin secretion were paralleled by dose-dependent changes in inositol phosphate (IP) production, indicating mediation by V1-type VP receptors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 26 publications
5
51
1
Order By: Relevance
“…On the other hand, AVP causes insulin release from pancreatic islets (262), which partially counteracts the effect of the AVP-induced rise in blood glucose. The AVP-induced hepatic glycogenolysis is mediated predominantly by the V1a receptor (250,348), and the AVP-stimulated insulin release from ␤ cells or glucagon release from ␣ cells of the pancreas is mediated by the V1b receptor (371,389,419,483). A further study with V1bR-KO mice and antagonists for the V1b or OT receptors indicated that the OT receptor is likely involved in the AVP-stimulated glucagon release (164).…”
Section: F Glucose Homeostasismentioning
confidence: 99%
“…On the other hand, AVP causes insulin release from pancreatic islets (262), which partially counteracts the effect of the AVP-induced rise in blood glucose. The AVP-induced hepatic glycogenolysis is mediated predominantly by the V1a receptor (250,348), and the AVP-stimulated insulin release from ␤ cells or glucagon release from ␣ cells of the pancreas is mediated by the V1b receptor (371,389,419,483). A further study with V1bR-KO mice and antagonists for the V1b or OT receptors indicated that the OT receptor is likely involved in the AVP-stimulated glucagon release (164).…”
Section: F Glucose Homeostasismentioning
confidence: 99%
“…This outward-rectifying K+ channel might play a role in the generation of the eccrine cell membrane potential, whilst the Ca2+-activated K+ channel might be involved in secretory or absorptive events. Recent work has localized vasopressin immunologically in human and rat pancreas (Amico et al 1988) and in the insulin secreting HIT cell line VP caused a rapid and sustained release of insulin (Richardson et al 1990). The mechanism of insulin release by VP is unclear.…”
Section: Pmentioning
confidence: 99%
“…10 In contrast, AVP inhibited glucose-induced insulin release in rat islets 21 and in clonal /3-cells HIT-T15. 22 AVP (1-100 nmol/1) failed to stimulate somatostatin release in the absence of extracellular glucose, however, AVP increased somatostatin release in the presence of glucose mmol/L). 20 Since there are discrepancies in the effects of AVP on the endocrine pancreas, insulin release in particular, the present study was designed to study the direct effect of AVP (30 or 300 pmol/L) on insulin, glucagon and somatostatin release from the perfused rat pancreas in the presence of various glucose concentrations (0,1.4, 5.5, or 20 mmol/L).…”
mentioning
confidence: 86%
“…[11][12][13][14][15] AVP may regulates glucose metabolism by its direct glycogenolytic and gluconeogenic effects on the liver 4 , and by modulating insulin and glucagon release from the endocrine pancreas. The fact that AVP is present in the pancreas 3 suggests that AVP may exert a local control on the endocrine pancreas.…”
mentioning
confidence: 99%